The early use of Antibiotics for at Risk CHildren with InfluEnza-like illness (ARCHIE): a double-blind randomised placebo-controlled trial - Wang, K; Semple, MG; Moore, M; Tonner, S; Galal, U; Grabey, J; Carver, T; Perera, R; Yu, L-M; Mollison, J; Farmer, A; Butler, CC; et al. (European Respiratory Society, 2021)
Introduction The UK government stockpiles co-amoxiclav to treat bacterial complications during influenza pandemics. This pragmatic trial examines whether early co-amoxiclav use reduces re-consultation due to clinical deterioration in ‘at risk’ children presenting with influenza-like illness (ILI) in primary or ambulatory care. Methods ‘At risk’ children aged 6 months to 12 years presenting within five days of ILI onset were randomly assigned to oral co-amoxiclav 400/57 or placebo twice daily for five days (dosing based on age +/- weight). ‘At risk’ groups included children with respiratory, cardiac, and neurological conditions. Randomisation was stratified by region and used a non-deterministic minimisation algorithm to balance age and current seasonal influenza vaccination status. Our target sample size was 650 children, which would have allowed us to detect a reduction in the proportion of children re-consulting due to clinical deterioration from 40% to 26% with 90% power and 5% two-tailed alpha error, including allowance for 25% loss to follow-up and an inflation factor of 1.041. Participants, caregivers and investigators were blinded to treatment allocation. Intention-to-treat analysis included all randomised participants with primary outcome data on re-consultation due to clinical deterioration within 28 days. Safety analysis included all randomised participants. Trial registration: ISRCTN 70714783. EudraCT 2013-002822-21. Results We recruited 271 children between 11 February 2015 and 20 April 2018. Primary outcome data were available for 265 children. Only 61/265 children (23.0%) re-consulted due to clinical deterioration. No evidence of a treatment effect was observed for re-consultation due to clinical deterioration (co-amoxiclav 33/133 (24.8%), placebo 28/132 (21.2%), adjusted risk ratio [RR] 1.16, 95% confidence interval [CI] 0.75 to 1.80). There was also no evidence of a difference between groups in the proportion of children for whom one or more adverse events were reported (co-amoxiclav 32/136 (23.5%), placebo 22/135 (16.3%), adjusted RR 1.45, 95% CI 0.90 to 2.34). Sixty-six adverse events were reported in total (co-amoxiclav n=37, placebo n=29). Nine serious adverse events were reported per group; none were considered related to study medication. Conclusion Our trial did not find evidence that treatment with co-amoxiclav reduces risk of re-consultation due to clinical deterioration in ‘at risk’ children who present early with ILI during influenza season. Our findings therefore do not support early co-amoxiclav use in children with seasonal ILI.